Effects of an artificial blend of host‐infested plant volatiles on plant attractiveness to parasitic wasps. (20th May 2016) - Ohara, Y.; Uchida, T.; Kakibuchi, K.; Uefune, M.; Takabayashi, J.
Abstract: For the biological control of diamondback moth (DBM) larvae in commercial greenhouses, we have previously identified a blend of volatiles that attracted Cotesia vestalis, a parasitoid of DBM larvae. Here, we tested the effects of an artificial volatile blend on the attractiveness of komatsuna plants (Japanese mustard spinach; Brassica rapa var. perviridis ) to C. vestalis under greenhouse conditions. First, we showed that female C. vestalis preferred infested komatsuna plants to uninfested plants in the greenhouse. Under the same conditions, placing the artificial attractants near both infested and uninfested plants did not affect the wasps' preference. However, when comparing infested komatsuna plants coupled with the artificial attractants with infested plants without them, significantly more female C. vestalis were attracted to the former. The possible use of artificial C. vestalis attractants for the biological control of DBM is discussed.